Does cigarette smoking increase time to conception? - Munafo, M; Murphy, M; Whiteman, D; Hey, K (2002)
Data are reported on the relationship between cigarette smoking and other health-related behaviours and time to conception in a population-based sample of women who acted as a control group in a case-control study of twinning. Women who continued to smoke close to the time of conception took significantly longer to become pregnant than women who never smoked or stopped smoking before the year during which they attempted to conceive. A hierarchical regression analysis performed on time-to-conception data in women who continued to smoke in the year before conception provided weak evidence for a dose-response relationship between time to conception and number of cigarettes smoked per day. No significant relationships were found between time to conception and other health-related behaviours.